In memoriam of Oleksandra Petrivna Isaykina - Viktor Melnyk; Tetiana Bagatska; Nataliia Chuvikina; Svitlana Didenko; Nataliia Kushnir; Nadiia Dzhurenko (Інтродукція Рослин)
In February 8, 2025, the candidate of biological sciences (1973), laureate of the State Prize of Ukraine in Science and Technology (1992), author of ca. 80 scientific publications, Oleksandra Petrivna Isaykina, passed away. She was a friendly, sensitive and erudite person, sincerely devoted to botanical science. Oleksandra worked at the M.M. Gryshko National Botanical Garden of the NAS of Ukraine since 1984, holding the positions of senior and leading researcher. The major topic of her research activities were the resources of medicinal plants. She worked in the Department of Medicinal Botany, where she was the curator of the “Medicinal Plants” plot. After expeditions to the Danube Plains Nature Reserve, she created a motherwort of selected forms of sea buckthorn, which served as the basis for industrial culture. Later, while working in the Department of Natural Flora, she was the head of the Herbarium, where she organized the card index, conducted an inventory of several families, and processed the Far Eastern herbarium of Sigismund Kharkevich, which he donated to the botanical garden.